2014
DOI: 10.1111/gwmr.12055
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Apatite Permeable Reactive Barrier for In Situ 90Sr Immobilization

Abstract: An injectable permeable reactive barrier (PRB) technology was developed to sequester 90Sr in groundwater through the in situ formation of calcium‐phosphate mineral phases, specifically apatite that incorporates 90Sr into the chemical structure. This injectable barrier technology extends the PRB concept to sites where groundwater contaminants are too deep or where site conditions otherwise preclude the application of more traditional trench‐emplaced barriers. An integrated, multiscale development and testing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…It is known that apatite minerals are very stable in water; the solubility product of hydroxy- term, the precipitate formed in the conditions similar to this study is amorphous and poorly crystalline monocalcium phosphate (Moore et al, 2004;Vermeul et al, 2014). The formation of amorphous and poorly crystalline monocalcium phosphate occurs within a week, while crystalline apatite forms within a few weeks (Vermeul et al, 2014). Therefore, the migration of the Sr concentration profile may be due to the dissolution of amorphous calcium phosphate upon supply of the groundwater with low ionic strength.…”
Section: Reaction Mechanisms and Implications To Field Applicationsmentioning
confidence: 56%
See 2 more Smart Citations
“…It is known that apatite minerals are very stable in water; the solubility product of hydroxy- term, the precipitate formed in the conditions similar to this study is amorphous and poorly crystalline monocalcium phosphate (Moore et al, 2004;Vermeul et al, 2014). The formation of amorphous and poorly crystalline monocalcium phosphate occurs within a week, while crystalline apatite forms within a few weeks (Vermeul et al, 2014). Therefore, the migration of the Sr concentration profile may be due to the dissolution of amorphous calcium phosphate upon supply of the groundwater with low ionic strength.…”
Section: Reaction Mechanisms and Implications To Field Applicationsmentioning
confidence: 56%
“…Emplacement of apatite precipitate by solution injection has significant advantages over other apatite emplacement methods (e.g., minimal disturbance of the subsurface). This method extends the PRB concept to sites where groundwater contaminants are too deep or where site conditions otherwise preclude the application of more traditional trench-emplaced barriers (Vermeul et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of an apatite permeable reactive barrier (PRB) technology for in situ sequestration of strontium-90 ( 90 Sr) has been previously demonstrated on the Hanford Site (Vermeul et al 2014). Fullfield-scale application of this technology as a remedial alternative addressing a groundwater contaminant plume beneath the Hanford 100-N Area provides some advantages to this technology over other less welldeveloped technologies, because currently available technical expertise and regulatory/stakeholder familiarity with the apatite technology can be leveraged.…”
Section: In Situ Sequestration By Apatitementioning
confidence: 99%
“…To demonstrate its efficacy as a PRB, an experimental apatite barrier was deployed in the subsurface in 2005 (Figure 7-2) along a 300-foot-long section of Columbia River shoreline to prevent radioactive strontium from reaching the river. The barrier was then field-tested by Pacific Northwest National Laboratories (PNNL) and Fluor Hanford Inc. After six years, (2005)(2006)(2007)(2008)(2009)(2010)(2011) monitoring of wells drilled between the barrier and the Columbia River demonstrated that the barrier sequestered an average of 95 percent of the strontium before it could reach the river (Vermuel et al, 2014).…”
Section: Csts For Radioactive Cesium Remediationmentioning
confidence: 99%